A Conference Built on Trust - DeWinter, Deborah Hafner (Refuge: Canada’s Journal on Refugees, 2001)
In April 2001, 265 participants from twenty countries including representatives of the governments, intergovernmental organizations, non-governmental organizations, UNHCR, and former refugees met in Norrköping, Sweden, for the International Conference on the Reception and Integration of Resettled Refugees. Fundamentally, the success of the conference resulted from the overarching operating principles in the planning process which affirmed that all resettlement countries, traditional or emerging, had something positive and unique to contribute, and that no hierarchy would influence the equal value of comments made. As a result, a spirit of cooperation and trust was built that characterised the spirit of the conference and continues to influence the post-conference phase of the Integration Initiative.